Archaeological Excavations at 44JC568, The Reverend Richard Buck Site - Mallios, Seth (the Digital Archaeological Record)
Archaeologists from the Association for the Preservation of Virginia Antiquities (APVA), excavated archaeological site 44JC568 during the summers of 1996 and 1997. The work in 1996 was conducted from June 17th to July 26th by 13 field school students earning credits from the University of Virginia. In 1997, 18 field school students, again earning credits from the University of Virginia, worked at the site from June 30th to July 25th. Archaeologists named the site after the area’s first documented land owner, the Reverend Richard Buck, who served as the minister at Jamestown from 1610 to 1624. The Buck site, located in James City County, Virginia, on a parcel known as Neck-of-Land in the Peleg’s Point residential subdivision, is approximately one mile north of Jamestown Island. This report summarizes findings from 44JC568. The artifacts recovered from the site indicated it was occupied from ca. 1630-50. Historical records included details of Richard Buck’s 1619 patent on 750 acres of land at Neck-of-Land, bounded by Mill Creek on the east, Back River on the south, and Powhatan Creek on the west. It is unlikely that the Reverend himself lived at Neck-of-Land, residing instead at Jamestown. Upon Buck’s death in 1624, the property passed into the hands of a caretaker and guardian of his children, Richard Kingsmill. In 1635, Thomas Crump, husband of Richard Buck’s eldest daughter Elizabeth, acquired the 500 acres directly to the north of the original 750-acre Buck land patent. Buck’s eldest son Gercian attained his majority in the early 1630s, and in 1636 purchased the 500 acres from his brother-in-law, Thomas. Through this acquisition and the inheritance of his father’s Neck-of-Land property, Gercian amassed a contiguous 1,250-acre tract of land. Two years later, the youngest Buck sibling, Peleg, inherited the entire property upon Gercian’s death. Peleg held the land until his own demise in 1642, whereupon Elizabeth Crump assumed ownership until 1654. Due to the changing ownership of the property between 1619 and 1654, site 44JC568 likely related to a series of resident and non-resident owners, as well as groups of indentured servants and tenants. During the two summer field seasons, archaeological crews located and excavated a total of 53 features at 44JC568. These included three barrel lined wells, nine human burials, four small outbuildings, two pits, a series of ditches and fence lines, and additional miscellaneous soil discolorations and anomalies. The site yielded more than 12,000 artifacts, consisting primarily of poottery, case-bottle glass, clay tobacco pipe stems and bowls, nails and other iron objects, and faunal remains. Analysis of the findings suggested that the site served as a farmstead for a series of occupants. The artifact collection and archaeological context offered insights into the outfitting and operation of one of Virginia’s earliest attempts at settling Jamestown’s hinterland.